DEVELOPMENT OF PHYSICS E-LKPD WITH 3D PAGE FLIP BASED ON PROBLEM-BASED LEARNING ON STATIC ELECTRICITY - Aisyah Evi Nurhidayah; Handoyo Saputro; Puji Hariati Winingsih (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
This study aims to determine the quality and response of students to E-LKPD Physics. based on problem-based learning on static electricity material, developed to assist students in learning during the covid-19 pandemic for education which is required to learn online. This type of research is research and development (Research and Development) according to Sugiyono which is simplified into eight stages which include potential and problems, gathering product design information, product validation, product revision, product testing, product revision, and final product. The subjects of this study consisted of three validators and 16 students. Data analysis was carried out by descriptive analysis. The results of the feasibility test of the E-LKPD product obtained criteria for Very Good (68.11%), Good (29.71%), Less Good (2.18 % ), Very Poor ( 0% ) by the validator, and very good (100%) by student responses. Based on the test results, it can be concluded that the E-LKPD is suitable for learning physics.